ALLES ØYNE PÅ BROADWAY AMERIKANSK INNFLYTELSE PÅ MUSIKALSCENEN I NORGE - Svendal, Sigrid Øvreås (Temp - tidsskrift for historie, 2013)
ABSTRACT All Eyes on Broadway: American Influence on Musicals in Norway American musicals dominated the Norwegian theatre stages in the decades after 1945. Musicals like Oklahoma!, Kiss me Kate, Annie get your gun and West Side Story premiered in Norway between 1949 and 1965. How and why did the American musical become so popular? This article uses the musicals Kiss me Kate and West Side Story as case-studies, and shows how important individuals were as transfer channels. These individuals were highly transnational – using all of Scandinavia as work area. Musicals were regarded as American and were often defined as popular culture, rather than high culture. Furthermore, the article discussed different reasons for why the American musicals became so popular. The American musicals did not play an important part in the American cultural diplomacy program during the Cold War, and their impact can’t be explained by this motivation. The success of the American musicals can, however, be explained by a general orientation towards U.S. and American culture in the Scandinavian public, and the fact that both content and form appeared more interesting and modern than the previous European operettas that used to dominate the Norwegian theatres.